Associations of work hours with carotid intima–media thickness and ankle–brachial index: the Multi-Ethnic Study of Atherosclerosis (MESA). Issue 10 (5th July 2012) - Charles, Luenda E; Fekedulegn, Desta; Burchfiel, Cecil M; Fujishiro, Kaori; Landsbergis, Paul; Diez Roux, Ana V; MacDonald, Leslie; Foy, Capri G; Andrew, Michael E; Stukovsky, Karen H; Baron, Sherry
Abstract : Objectives: Long working hours may be associated with cardiovascular disease (CVD). The objective was to investigate cross-sectional associations of work hours with carotid intima–media thickness (CIMT) and ankle–brachial index (ABI). Methods: Participants were 1694 women and 1868 men from the Multi-Ethnic Study of Atherosclerosis. CIMT and ABI were measured using standard protocols. Information on work hours was obtained from questionnaires. Mean values of CIMT and ABI were examined across five categories of hours worked per week (≤20, 21–39, 40, 41–50 and >50) using analysis of variance/analysis of covariance. p Values for trend were obtained from linear regression models. Results: Mean age of participants was 56.9±8.4 years; 52.4% were men. Distinct patterns of association between work hours and the subclinical CVD biomarkers were found for women and men, although this heterogeneity by gender was not statistically significant. Among women only, work hours were positively associated with common (but not internal) CIMT (p=0.073) after full risk factor adjustment. Compared with women working 40 h, those working >50 h were more likely to have an ABI <1 (vs 1–1.4) (OR=1.85, 95% CI 1.01 to 3.38). In men, work hours and ABI were inversely associated (p=0.046). There was some evidence that the association between work hours and ABI was modified by occupational category (interaction p=0.061). Among persons classified as management/professionals, longer work hours was associated with lower ABI (p=0.015). No significant associations were observed among other occupational groups. Conclusions: Working longer hours may be associated with subclinical CVD. These associations should be investigated using longitudinal studies.